Industrial training: challenges among students in construction industry - Unadam, Faridatul Asma; Mohamad, Mimi Mohaffyza (2022)
Industrial training is structured learning off -campus and gives students the opportunity to gain experience in a professional field before they step into the real world of work. This study was conducted to find out the extent of the challenges faced by students during industrial training in terms of knowledge, skills, and work ethic. This study was conducted in a survey using a quantitative approach. Research applied the survey research design based using quantitative approach. A set of instruments developed based on literature analysis. The variables investigate are knowledge and skills in terms of challenges among student during industrial training period. The respondents from students in program related with Civil Engineering and Building Construction are involved to response the survey. There are 208 students from three faculties involved in this research. The findings of the study show that the challenges of students in terms of knowledge, skills and work ethic are at a high level, and there are differences between the three faculties in terms of knowledge, skills, and work ethics. As conclusion, students undergoing industrial training in Construction Industry are capable to apply knowledge and skills within the training period.